East Java Manufacturing Sector Growth Dynamics: Need More Physical Capital or Quality of Labor? - Afin, Rifai (Journal of Developing Economies, 2017)
This paper identifies the dynamic pattern of East Java growth of manufacturing sector and addresses the basic questions of individual economic firms whether they would be better off if increasing physical capital or investment in human capital. To know which one of the two main inputs in industrial sector that is more needed than the other, the marginal productivity of each production factors must be identified. I estimate the models which accommodate the optimum input level by applying general method of moment (GMM) and panel instrumental variable (IV) techniques on some reduced form models. I find that on the demand function of labor and capital as the first step of IV or Two Stage Least Square (2SLS) show that the elasticity of both of them are inelastic and elasticity of labor demand is more sensitive than capital. In the production function as the second step, yields that the most productive production factors is labor so that investment in this factor production is beneficial for industrial growth in East Java. On the other side, the physical capital has not been reached the optimum level but the elasticity of capital in production is low. Hypothetically, the inelasticity of physical capital is because macroeconomic aspects which is monetary policy and expected economic situation. Considering these two arguments, quality of labor should be more concerned in the context of regional economy of East Java because capital aspect cannot be interfered at regional level at least for large capital scale.Keywords: Capital, Labor, Growth, General Method of Moment (GMM), Instrumental Variable (IV)JEL: C50, C33, C36, M51, L29, L60, O25, D22